2018
DOI: 10.1103/physrevmaterials.2.024406
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion morphology in ultrathin magnetic films

Abstract: Nitrogen-vacancy magnetic microscopy is employed in quenching mode as a non-invasive, high resolution tool to investigate the morphology of isolated skyrmions in ultrathin magnetic films. The skyrmion size and shape are found to be strongly affected by local pinning effects and magnetic field history. Micromagnetic simulations including a static disorder, based on the physical model of grain-to-grain thickness variations, reproduce all experimental observations and reveal the key role of disorder and magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 47 publications
9
49
0
Order By: Relevance
“…Specifically, we have demonstrated that NV microscopy can simultaneously locally probe both magnetic structure and dynamics. As shown in similar thin film systems [25], pinning and disorder are important factors in determining static skyrmion bubble sizes in Ta/CoFeB/MgO. We have shown that these sizes are determined dynamically, via hopping of skymion bubble domain walls between pinning sites.…”
Section: Discussion and Future Nv Studies Of Skyrmionssupporting
confidence: 64%
See 1 more Smart Citation
“…Specifically, we have demonstrated that NV microscopy can simultaneously locally probe both magnetic structure and dynamics. As shown in similar thin film systems [25], pinning and disorder are important factors in determining static skyrmion bubble sizes in Ta/CoFeB/MgO. We have shown that these sizes are determined dynamically, via hopping of skymion bubble domain walls between pinning sites.…”
Section: Discussion and Future Nv Studies Of Skyrmionssupporting
confidence: 64%
“…Several imaging techniques have already been used to study skyrmions, including Kerr microscopy [10,14], Lorentz transmission electron microscopy [15,16], transmission X-ray microscopy [9], and magnetic force microscopy [12]. While each of these tools has certain advantages, a scanning probe microscope (SPM) based on the nitrogen-vacancy (NV) defect in diamond [17][18][19] is another probe particularly well-suited to studying skyrmion devices; the NV-SPM is magneti-cally non-invasive and offers quantitative, nanoscale spatial resolution of stray magnetic fields over a wide range of temperatures and magnetic fields [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This stochastic behavior can be attributed to the presence of pinning sites obstructing the skyrmion motion [22,23]. This local disorder can also ex-plain the large dispersion observed in the skyrmion size and shape [24][25][26] with a measured average effective diameter d Sk = 156 ± 45 nm (see Sec. 1.4 within the Supplementary Material).…”
Section: A Experimental Resultsmentioning
confidence: 97%
“…The skyrmion at rest is also distorted, since it relaxes on an inhomogeneous energy landscape, explaining the (static) deformation of some skyrmions in Fig. 1 [24][25][26]. Fig.…”
Section: Micromagnetic Simulationsmentioning
confidence: 94%
“…M agnetic skyrmions are nano-scale or meso-scale whirling spin configurations of topological nature which gives them some stability and long lifetime. Magnetic skyrmions have been found in a variety of non-centrosymmetric magnets 1 , in ultrathin magnetic films [2][3][4] , as well as in multiferroic insulators [5][6][7] . Quite remarkably, magnetic skyrmions can be stabilized over a wide temperature domain ranging from room temperature 8,9 to cryogenic temperature 2,3,10 .…”
mentioning
confidence: 99%